Human Umbilical Cord Stem Cell Xenografts Improve Cognitive Decline and Reduce the Amyloid Burden in a Mouse Model of Alzheimer's Disease - Boutajangout, Allal; Noorwali, Abdulwahab; Atta, Hazem; Wisniewski, Thomas (Current Alzheimer Research, 2017)
Introduction: Alzheimer's disease (AD) is the most common cause of dementia. The search for new treatments is made more urgent given its increasing prevalence resulting from the aging of the global population. Over the past 20 years, stem cell technologies have become an increasingly attractive option to both study and potentially treat neurodegenerative diseases. Several investigators reported a beneficial effect of different types of stem or progenitor cells on the pathology and cognitive function in AD models. Mouse models are one of the most important research tools for finding new treatment for AD. We aimed to explore the possible therapeutic potential of human umbilical cord mesenchymal stem cell xenografts in a transgenic (Tg) mouse model of AD. Methods: APP/PS1 Tg AD model mice received human umbilical cord stem cells, directly injected into the carotid artery. To test the efficacy of the umbilical cord stem cells in this AD model, behavioral tasks (sensorimotor and cognitive tests) and immunohistochemical quantitation of the pathology was performed. Results: Treatment of the APP/PS1 AD model mice, with human umbilical cord stem cells, produced a reduction of the amyloid beta burden in the cortex and the hippocampus which correlated with a reduction of the cognitive loss. Conclusion: Human umbilical cord mesenchymal stem cells appear to reduce AD pathology in a transgenic mouse model as documented by a reduction of the amyloid plaque burden compared to controls. This amelioration of pathology correlates with improvements on cognitive and sensorimotor tasks.
Keywords: stem cell